Transverse photonic crystal semiconductor laser arrays. (1st September 2022) - Fu, Ting; Chen, Jingxuan; Fan, Jian; Wang, Yufei; Zhou, Xuyan; Qi, Aiyi; Wang, Xueyou; Xing, Xiaoxu; Wang, Liang; Qu, Hongwei; Dai, Yingqiu; Wang, Mingjin; et al.
Abstract: Transverse photonic crystal (TPC) laser arrays are designed by effective index method and transfer matrix method, and fabricated by the process of standard photolithography. The fundamental supermode of the TPC laser array possesses a larger optical confinement factor in the active region than those of high-order supermodes, because the propagation constant of the fundamental supermode lies in the forbidden band of the TPC while all the propagation constants of the high-order supermodes lie in the allowed band of the TPC. Therefore, the fundamental supermode can lase firstly near the threshold when the laser is injected with currents. The fabricated TPC laser achieves a single-lobe horizontal far-field pattern under an injection current of 0.3 A, and the corresponding near-field pattern is well confined to the center five waveguides injected with currents. The TPC semiconductor laser array may be a good candidate for optical sources with narrow horizontal divergence angles.